2005
DOI: 10.1086/428568
|View full text |Cite
|
Sign up to set email alerts
|

ChandraObservations of MBM 12 and Models of the Local Bubble

Abstract: Chandra observations toward the nearby molecular cloud MBM 12 show unexpectedly strong and nearly equal foreground O viii and O vii emission. As the observed portion of MBM 12 is optically thick at these energies, the emission lines must be formed nearby, coming from either the Local Bubble (LB) or charge exchange with ions from the Sun. Equilibrium models for the LB predict stronger O vii than O viii, so these results suggest that the LB is far from equilibrium or that a substantial portion of O viii is from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
3

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(75 citation statements)
references
References 58 publications
(82 reference statements)
4
68
3
Order By: Relevance
“…In Figure 4, Foreground emission taking into account the optical depth of the shadows. Data taken from Smith et al (2005Smith et al ( , 2007; Henley & Shelton (2008); Gupta et al (2009) controversy of the dominant emission mechanism in the local interstellar inedimn. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Figure 4, Foreground emission taking into account the optical depth of the shadows. Data taken from Smith et al (2005Smith et al ( , 2007; Henley & Shelton (2008); Gupta et al (2009) controversy of the dominant emission mechanism in the local interstellar inedimn. …”
Section: Resultsmentioning
confidence: 99%
“…The perfect candidate for this kind of observing strategy is NIBM 12, a nearby high-galactic (l, b -159°, -34°), low-ecliptic (A, (3 47°, 3") latitude molecular cloud , with a column density of -4x 1021 c111-2 (Smith et al 2005), which is optically thick for the oxygen lines energies that are of interest in our analysis (optical depths of 3.5 and 2.4 for O VII and O VIII respectively). Early estimates of the distance to NIBM 12 were controversial and have placed it between 65 and 360 pc (Hobbs et al 1986;Andersson et al 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the column density, apart from during the outburst itself, has remained fairly constant throughout these observations at about 4−5 × 10 22 cm −2 . Smith et al (2005) show that the hydrogen column density due to the MBM12 molecular cloud varies across the cloud between 2−15 × 10 21 cm −2 . This suggests that a column density of at least 3 × 10 22 cm −2 is intrinsic to XY Ari.…”
Section: A Continued Decline From Outburst?mentioning
confidence: 94%
“…In addition to the pioneering work noting the so-called Long Term Enhancements (subsequently known to be due to SWCX emission) within ROSAT observations (Snowden et al 1995), the assignment of such enhancements to SWCX emission has also been observed in studies undertaken using data from Suzaku (Fujimoto et al 2007;Bautz et al 2009) and Chandra (Smith et al 2005). Enhancements in soft X-ray band XMM-Newton spectra have been attributed to SWCX contamination in the literature (Snowden et al 2004;Kuntz & Snowden 2008;Snowden et al 2009;Henley & Shelton 2008).…”
Section: Introductionmentioning
confidence: 92%